The Concept of Identity and it’s Policies – Study on issues of Diversity and Difference - Almustafa, Raad Abduljalil Ali; Mawlood, Imad Ahmad (Journal of Legal and Political Studies, 2019)
The issue of identity and identity conflicts between the state and cultural groups is a modern issue that has taken place in a wide range of international political and academic debates and renewed interest since the end of the Cold War. Freedoms and social justice of the social and political movements that have emerged in the hearts of the developed countries and all the hidden in their own form and features since the sixties of the twentieth century. This research tackles this problem from the discussion of the concept of identity, which is reflected in the formula of the parallel binaries (fate, autonomy, objectivity, …. etc.), as well as the discussion of identity policies, Thus ensuring the rights and freedoms of cultural groups, as well as the ability of the State to remain neutral towards identity conflicts. and the problematic relationship between national identity in the sub-identities and the role of the state in building a national identity. All these issues are the subject of debate between supporters of individual liberalism and community liberalism .
Keywords: Identity; Identity Policies; Diversity; Difference; Cultural Groups; National Identity; Subidentities